Sintesis Senyawa C-Vanillin Kaliks[4]resorsinarena dan Uji Aplikasinya sebagai Adsorben Ion Fe³⁺: Studi Optimasi pH - Nurul Afifah; Sri Benti Etika (Lembaga Yasin AlSys, 2025)
This study is driven by the need for selective and efficient adsorbent materials to address heavy metal ion contamination, particularly Fe³⁺, in aquatic environments. The aim of this research is to synthesize C-vanillin calix[4]resorcinarene and evaluate its potential as an adsorbent for Fe³⁺ ions, with a specific focus on optimizing pH as a key parameter in the adsorption process. The compound was synthesized via a reflux method, yielding a solid product weighing 3.9726 grams. Structural characterization was performed using Thin-Layer Chromatography (TLC), FTIR spectroscopy, and melting point analysis. TLC results showed a single spot for each compound, indicating high purity. The FTIR spectrum confirmed the presence of characteristic functional groups, with absorption bands at 3355 cm⁻¹ (O–H), 1605 cm⁻¹ (aromatic C=C), 1426 cm⁻¹ (C–H), and 1211 cm⁻¹ (C–O). The high melting point range of 383–384 °C suggests thermal stability and the formation of a new structure. Adsorption tests for Fe³⁺ ions were conducted across a pH range of 1–6, revealing increased adsorption efficiency with rising pH and a maximum value of 1.9015 mg/g at pH 5. A decline in efficiency was observed at pH 6. The study concludes that C-vanillin calix[4]resorcinarene demonstrates promising selectivity and efficiency as an Fe³⁺ ion adsorbent under specific pH conditions and possesses physicochemical properties conducive to practical applications in water purification.